Investigation of structure, dielectric properties, and AC conductivity at high temperature for chitosan capped metal oxides nanocomposites - Ali H. Bashal; Nazeeha S. Alkayal; Jeenat Aslam; Khaled D. Khalil (Journal of Taibah University for Science)
In this study, chitosan (CS)-based nanocomposite films incorporating CoO, SrO, AgO, and CeO nanoparticles were synthesized via solution casting. Structural characterization using FTIR and XRD confirmed the successful integration of metal oxide nanoparticles into the chitosan matrix. The dielectric and AC conductivity properties were examined as a function of frequency at 120 °C. The nanocomposites exhibited frequency-dependent dielectric behavior, where permittivity and dielectric loss decreased with increasing frequency. AC conductivity remained stable at low frequencies and increased linearly at higher frequencies, indicating enhanced charge transport. Additionally, electric modulus analysis provided insights into the relaxation behavior of the films. The incorporation of metal oxides significantly enhanced the electrical performance of the chitosan matrix. These improvements suggest that such nanocomposites are promising for applications in electrochemical devices, energy storage, sensors, and optoelectronics due to their superior dielectric and conductive properties.